Potential of NIRS for determining multiple cannabinoid concentrations in Cannabis sativa L. - Tina Sullivan; Matt Yost; Earl Creech; Bruce Bugbee (Agrosystems, Geosciences & Environment)
Abstract Following the 2018 Farm Bill, many US states allowed for hundreds of industrial hemp licenses, and the resulting production flooded markets. Floral industrial hemp (Cannabis sativa L.) offered prospects in essential oils for medicinal, flavoring, and fragrance additives. One major limitation for growers is the expense of Δ9‐tetrahydrocannabinol (Δ9THC) monitoring to meet legal compliance while maximizing cannabidiol (CBD) or cannabigerol (CBG) concentration for financial return. Cannabinoid analysis is not widely available, and shipping samples is legally challenging with state‐by‐state legislation. The study objectives were to evaluate whether near‐infrared spectroscopy (NIRS) could be used to rapidly and inexpensively quantify commonly produced hemp cannabinoid concentrations compared to industry standard high‐performance liquid chromatography (HPLC). A total of 448 tissue samples from 3 years of outdoor hemp cultivar, irrigation, and fertility trials were evaluated. Samples were dried and ground, and Δ8‐tetrahydrocannabinol (Δ8THC), Δ9THCD, tetrahydrocannabinolic acid (THCA), CBD, CBG, cannabichromene (CBC), cannabinol (CBN), cannabidivarin (CBDV), cannabidiol acid (CBDA), and cannabigerol acid (CBGA) were determined by HPLC with a diode array detector as reference measurements, prior to analysis by NIRS. Calibration equations were developed to assess whether NIRS can estimate cannabinoid concentrations. The three cannabinoids of most importance for floral hemp production (THCA, CBDA, and CBD) had the widest range in concentrations and the best correlation (R2 = 0.71–0.87) between NIRS and HPLC, while other cannabinoids had limited concentration ranges and poorer correlation. The THC and CBD results are highly encouraging and indicate that NIRS is a robust tool for rapid and inexpensive quantification.